Perkembangan Komunitas Arab di Indonesia : Studi Kasus Perkampungan Masyarakat Arab di Pekojan Jakarta Barat pada Tahun 1950-2018 - Rizal Nasser; Sulasman Sulasman; Mahbub Hefdzil Akbar (Historia Madania: Jurnal Ilmu Sejarah, 2020)
Pekojan village is one of the urban villages that has a historical role in the development of the Arab community in the city of Jakarta. Part of the Arabs living in the Pekojan village have developed rapidly, especially in trading, preaching, education and marriage. This activity has an impact on social relations between Arabs and the Indigenous population. With very close social relations activities, the Arabs were well received by the Indigenous population. However, most of the Arabs living in the Pekojan village moved to around Jakarta. The purpose of this research is to identify Arab communities spread across Indonesia and to know the development of Arab society in the form of social relations and activities in the Pekojan village, Jakarta. The method used in research is a qualitative method, namely by collecting data through literature and documentation. Data analysis techniques with heuristic methods, criticism, interpretation and historiography. The results of the study that in the 18th century the migration of Arabs had a considerable impact on the development of the Arab community in Indonesia, especially on the island of Java. In the 19th century the wijeknstelsel policy had an impact on Arabs who came from Hadarmaut to occupy Pekojan village as a village inhabited by Arabs, such as in Pekojan village, Jakarta. In the 20th century, the Pekojan village began to be very different, some Arabs moved to around Jakarta some still settled and also built social relations and activities with the Indigenous population.